SPP1 as a biomarker for idiopathic membranous nephropathy progression and its regulatory role in inflammation and fibrosis - Pang, Shuting; Zhou, Rongbin; Liu, Zige; Xie, Boji; Liu, Fugang; Feng, Bingmei; Chen, Xuesong; Ruan, Liangping; Chen, Hong; Xie, Yuli; Tan, Qiuyan; Zhao, Binran; et al. (Frontiers in Immunology, 2025)
ObjectiveIdiopathic membranous nephropathy (IMN) is a leading cause of nephrotic syndrome in middle-aged and elderly populations. Early intervention can delay disease progression and improve patient outcomes. This study aims to identify urinary biomarkers for IMN and investigate their association with disease progression, offering new insights for precise diagnosis and treatment.MethodsThis study began with RNA sequencing of three urine sample types (first-void morning urine, second-void morning urine, and random urine), combined with single-cell RNA sequencing of renal tissues. Bioinformatics analyses—including differential gene expression screening, machine learning, and molecular function annotation—were employed to identify potential IMN biomarkers. Furthermore, we established both a siRNA-mediated gene silencing model and a lentivirus transfection-mediated gene overexpression model in HK-2 cells. Subsequently, we investigated the functional mechanisms of the candidate biomarkers through qRT-PCR, Western blot, immunohistochemistry, and immunofluorescence assays.ResultsSPP1 was identified as a promising biomarker for IMN, demonstrating a critical role in promoting fibrosis and inflammatory responses associated with the disease. These findings suggest its potential as a novel therapeutic target for IMN intervention.